Utilization of Health Belief Model as a Guide for Prediction of Breast Self-Examination - Al- Battawi, Jilan Ali; Sofar, Samah Mahmoud (International Journal For Research In Health Sciences And Nursing, 2018)
Breast cancer is currently the most prevalent cancer among women in both the developed and developing countries. American Cancer Society estimated that there were 175, 000 new cases of invasive breast cancer and 40,000 new cases of breast cancer in situ in the primary stage women. About 95% of all breast cancers can be early detected by breast self examination (BSE). The Health Belief Model (HBM) is a conceptual model that has been used to predict health related behaviors. Aim of the study: Using of Health Belief Model as a Guide for Prediction of Breast SelfExamination. Materials and Method: A quantitative descriptive correlational cross-sectional research design was used to carry out this study. Setting: The study was conducted from February 2017 up to April, 2017 at, Main University Hospital, Alexandria, Egypt. Subjects: A total of 120 eligible women attending the outpatient clinic at Main University Hospital in Alexandria were selected to participate in the study. Two Tools were used to collect the necessary data for the research. Tool I: Sociodemographic characteristics and clinical data structured interview questionnaire. It was divided into two parts. Part one: Concerned with participants’ Socio demographic data pertaining to age, marital status, level of educational, and level of income. Part two: Concerned with clinical data of the participants such as history of breast problems, heard about BSE, performing BSE, family’ history of breast cancer and sources of information. Tool II: Champion Health Belief Model Scale (CHBMS). It is consisted of 31 items; perceived of susceptibility (3 items) perceived seriousness (6 items), perceived benefits (4 items), perceived barriers (8 items), and perceived self- efficacy (10 items). All items were arranged in a Likert scale ranging from strongly disagree; scored: one to strongly agree; scored: five. Latest version of the statistical software package SPSS (Version-21) was used. Descriptive and analytical statistical test were used to analyze the data. Results: The mean age of participants was 32.2 (SD=8.1). there was statistically significant difference in relation to perceived benefits and self-efficacy and barrier between women performing and not performing breast self-examination (P = 0.03, 0.001 and 0.001) respectively. perceived self-efficacy was statistically significant positive predictors for BSE performance (p= 0.003) while, perceived barriers was statistically significant negative predictors (p= 0.001). Conclusion: Women performing breast self-examination had more perceived benefits and self-efficacy than women who not performing. Moreover, there was statistically significant difference regarding BSE perceived barrier between women performing and not performing breast self-examination. perceived self-efficacy was statistically significant positive predictors for BSE performance while, barriers was statistically significant negative predictors for BSE performance.